Plantar forefoot pain due to vascular leiomyoma: a case report - Prado Pereira, Tomas Araujo; de Lima, Everton; Lompa, Paulo Arlei; Maineri, Marcelo de Oliveira (Scientific Journal of the Foot & Ankle, 2018)
The diagnosis of plantar forefoot pain is very extensive. Plantar pain in the forefoot usually occurs due to mechanical aetiologies such as metatarsalgia, stress fractures and nerve damage. Tumours are a rare cause of plantar pain in the forefoot. We report the case of a patient with chronic pain in the plantar region of the forefoot due to a vascular leiomyoma. Level of Evidence V; Diagnostic Studies; Expert Opinion.